The Influence of Leadership Style, Organizational Communication Satisfaction, and Organizational Support on Employee Work Motivation Moderated by Psychological Resilience at Cilandak Marines Hospital - ARYA WIRA TAMA; AKHIYAR MEIDERI (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Digital transformation requires organizations to strengthen human motivation and resilience. This study aims to examine the influence of Leadership Style, Organizational Communication Satisfaction, and Organizational Support on Employee Work Motivation, with Psychological Resilience as a moderating variable at Cilandak Marines Hospital. This research applied a quantitative approach using a survey method involving employees at Cilandak Marines Hospital. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) through SmartPLS. The analysis consisted of measurement model evaluation, structural model evaluation, and hypothesis testing using bootstrapping. The model examined direct relationships between variables and the moderating effect of Psychological Resilience. The results show that all hypotheses are accepted. Leadership Style has a positive and significant effect on Employee Work Motivation with an original sample value of 0.284, t-statistic 3.921, and p-value 0.000. Organizational Communication Satisfaction also has a significant effect with an original sample value of 0.231, t-statistic 3.115, and p-value 0.002. Organizational Support provides the strongest influence with an original sample value of 0.356, t-statistic 5.284, and p-value 0.000. Furthermore, Psychological Resilience significantly strengthens the relationship between Leadership Style, Organizational Communication Satisfaction, and Organizational Support toward Employee Work Motivation. The study concludes that organizational factors and employee psychological resilience are essential in improving motivation. Organizations should develop supportive leadership, effective communication, employee support systems, and resilience programs to sustain employee performance and motivation.